Strategi Keluarga Nelayan dalam Mengatasi Kesulitan Ekonomi terhadap Akses Pendidikan Anak Nelayan di Tapian Nauli I Kecamatan Tapian Nauli Kabupaten Tapanuli Tengah - Ernawati Harefa; Sakti Ritonga (Jurnal Eduslamic, 2026)
This study examines the economic conditions of fishing families, analyzes their children's access to education, and investigates the strategies employed to overcome financial barriers to schooling in Tapian Nauli I Village, Central Tapanuli Regency, Indonesia. Employing a descriptive qualitative approach, data were collected through observations, in-depth interviews, and documentation. Informants, selected via purposive sampling, included fishing families, the village head, and customary leaders. The findings reveal that the economic situation of fishing families is highly precarious, fluctuating significantly with weather patterns and fishing seasons. This income instability directly impedes their capacity to finance their children's education. Barriers to educational access are multifaceted, encompassing financial constraints, the absence of a senior high school within the sub-district, and, in some families, a low educational motivation. Despite these challenges, fishing families demonstrate agency by implementing four primary coping strategies: strict household economizing, income diversification (including wives' engagement in economic activities), utilization of social networks (such as rotating savings and mutual cooperation), and leveraging government assistance programs (like the Smart Indonesia Card-KIP Kuliah). Framed within Anthony Giddens' Structuration Theory, these findings underscore the concepts of agency, the duality of structure, and practical consciousness as crucial for understanding the dynamics of impoverished coastal communities.